2017
DOI: 10.1111/tran.12211
|View full text |Cite
|
Sign up to set email alerts
|

“My happiest time” or “my saddest time”? The spatial and generational construction of marriage among youth in rural Malawi and Lesotho

Abstract: Marriage among African teenagers is currently a central focus of campaigns by UN agencies and international NGOs. Yet marriage has received only limited attention from geographers and has largely escaped the attention of geographers of youth. In this paper we explore the relational geographies of age that underlie young people's motivations for, and experiences of, marriage in two rural African settings with differing marriage practices: matrilocal southern Malawi and patrilocal Lesotho. We draw on participato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…Previous work exploring reasons for child marriage in Malawi found that most young women married because of poverty and, to a lesser extent, unplanned pregnancy [9], while education plays a protective role in delaying age at first marriage [10]. These findings are consistent with findings from other contexts in sub-Saharan Africa and South and Southeast Asia [3], [11], [12], [13], [14], [15].…”
supporting
confidence: 82%
“…Previous work exploring reasons for child marriage in Malawi found that most young women married because of poverty and, to a lesser extent, unplanned pregnancy [9], while education plays a protective role in delaying age at first marriage [10]. These findings are consistent with findings from other contexts in sub-Saharan Africa and South and Southeast Asia [3], [11], [12], [13], [14], [15].…”
supporting
confidence: 82%
“…The Young Lives findings resonate with insights from feminist scholars of development who, first, highlight the role of context in making sense of young women's choices and 'empowerment' (Cornwall and Edwards, 2010;Folbre, 1994). For example, attention to the everyday circumstances and material and cultural logics of motherhood in childhood would caution against simple attributions of either victimhood or agency to teenage mothers (Ansell et al, 2018). This requires moving beyond adult-centric approaches that tend to equate motherhood with women and that position children as dependent objects of adult care, these approaches reducing motherhood in childhood to problem, or even 'deviant', childhoods (Caputo, 2018).…”
Section: / 12mentioning
confidence: 73%
“…This work has been complemented by scholarship highlighting the need to recognise patriarchy's empirical complexity and institutional variations both spatially and temporally (Duncan, 1994; Hopkins, 2006; Jackson, 1991; Smith, 1990). In terms of geographical research on gender relations in Africa specifically, a rich body of work can be found using the previously mentioned approaches and addressing similar themes in the sub‐disciplines of critical development studies (Ardayfio‐Schandorf, 2002; Daley, 2008; Sharp et al., 2003) and geographies of children and youth (Ansell et al., 2018; Jones & Chant, 2009; Porter et al., 2011).…”
Section: Introductionmentioning
confidence: 99%